O Direito à saúde e a efetividade das garantias sociais na constituição de 1988: entre interpretação judicial, emendamento constitucional e fatores constitutivos da sociedade brasileira - SILVA, Paulo Henrique Araújo da (2022)
This monograph seeks to investigate how the phenomenon of the judicialization of health, in which standards of interpretation by the Supreme Court that call into question the very social nature of this right, raises questions involving the difficulties of implementing Social Rights in Brazil. Both points reflect a symptomatic problem of the 1988 Constitution in serving as an effective instrument for social demands given the interference of economic, legal and historical factors that compromise the realization of these rights, a matter of consequences beyond the demands brought to the Judiciary, being also perceived in the many and constant constitutional reforms by the Legislative Power, actions that, together, result in material restriction, in the form of interpretation of the Constitution, and formal restriction, in the form of constitutional amendment of several of the Social Rights enshrined in the constituent pact. Considering legal, philosophical and political factors, the research investigates this complex discrepancy between what the 1988 Constitution agreed in its text and what is effectively protected, through a bibliographical approach of a qualitative nature that tries to escape from mere empirical study or then from the typically descriptive and rigidly normative legal study. In order to understand the complex issue involving the effectiveness of Social Rights in Brazil, an interdisciplinary study must be carried out, considering not only theoretical and empirical research on the subject within the scope of Constitutional Law, but also studies in Political Philosophy and Political Science.